2022
DOI: 10.1108/ilt-07-2021-0281
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of influence of double-layer bump foils on aerodynamic thrust foil bearings performance

Abstract: Purpose Gas thrust foil bearings (GTFBs) are used to balance the axial load of engines. However, in some working conditions of large axial force, such as the use of single impeller air compressor, the load capacity of GTFBs is still insufficient. To solve this problem, the load capacity can be improved by increasing the stiffness of bump foil. The purpose of this paper is to explore a scheme to effectively improve the performance of thrust foil bearings. In the paper, the stiffness of bump foil is improved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Wire EDM cutting and die forming technology with MoS 2 coating were employed in foil fabrication as explained by RK Sahoo and others [34] in developing a TFB of 44 mm OD. Dynamic tests on AFTB with bump foil of 0.1 mm, 0.2 mm and double-layered 0.1 mm thicknesses indicated that double-layered bump foil and 0.2 mm bump foil had higher stiffness, higher damping, and higher load bearing capability with high energy consumption ability according to Xu and others [35]. A high speed bearing test rig comprising of a turbo-runner driven by a compressed air developed by Latray and Kim [36] measured the bearing load, torque, operating speed, frictional torque and foil surface temperature.…”
Section: Experimental Reviewmentioning
confidence: 81%
See 1 more Smart Citation
“…Wire EDM cutting and die forming technology with MoS 2 coating were employed in foil fabrication as explained by RK Sahoo and others [34] in developing a TFB of 44 mm OD. Dynamic tests on AFTB with bump foil of 0.1 mm, 0.2 mm and double-layered 0.1 mm thicknesses indicated that double-layered bump foil and 0.2 mm bump foil had higher stiffness, higher damping, and higher load bearing capability with high energy consumption ability according to Xu and others [35]. A high speed bearing test rig comprising of a turbo-runner driven by a compressed air developed by Latray and Kim [36] measured the bearing load, torque, operating speed, frictional torque and foil surface temperature.…”
Section: Experimental Reviewmentioning
confidence: 81%
“…6. Based on Xu et al [35] the GFTB of 25 mm OD (FSA = 1250 mm 2 ) operating at 24,000 rpm with 0.2 mm bump foil carried higher axial loads (107 N), when compared to that of a laborious double layered 0.1 mm bump foil (95 N). 7.…”
Section: Comparative Surveymentioning
confidence: 99%
“…In the vigorous development of fluid machinery and equipment, gas lubrication technology has been widely used and made great progress and has caused extensive research and discussion (Xu et al, 2022a(Xu et al, , 2022bZhou et al, 2022;Feng, 2021a, 2021b;Kumar et al, 2022aKumar et al, , 2022b. Generally, the micron-sized gas film thickness under lubrication makes the Knudsen number of the model in the slip flow, which makes bearing performance research work focus on the influence of rarefaction effect (Kumar et al, 2022a(Kumar et al, ,2022bXu et al, 2022aXu et al, , 2022b.…”
Section: Introductionmentioning
confidence: 99%
“…In the vigorous development of fluid machinery and equipment, gas lubrication technology has been widely used and made great progress and has caused extensive research and discussion (Xu et al, 2022a(Xu et al, , 2022bZhou et al, 2022;Feng, 2021a, 2021b;Kumar et al, 2022aKumar et al, , 2022b. Generally, the micron-sized gas film thickness under lubrication makes the Knudsen number of the model in the slip flow, which makes bearing performance research work focus on the influence of rarefaction effect (Kumar et al, 2022a(Kumar et al, ,2022bXu et al, 2022aXu et al, , 2022b. However, the surface roughness and gas film thickness are at the same micrometer scale (Zhang et al, 2021a(Zhang et al, , 2021b, which makes the surface roughness significantly affects the flow behavior and thermal performance of gas-lubricated bearings as well as the rarefaction effect.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of friction on double-layer foil thrust bearing performance was explored by Xu F C et al. 24 Experiment results indicated that double-layer foil thrust bearing had stronger ability to consume external energy comparing to single layer foil thrust bearing, and this type of bearing had greater damping.…”
Section: Introductionmentioning
confidence: 99%